IMMUNOLOGICAL CHARACTERISTIC OF A HEALTHY NEWBORN - Чистякова, Гузель Нуховна; Черешнев, Валерий Александрович; Ремизова, Ирина Ивановна; Ревер, Светлана Владимировна (Mother and Baby in Kuzbass, 2025)
Objective – to characterize the immune system of healthy newborns delivered by vaginal delivery.Materials and methods. A total of 50 healthy term infants discharged in satisfactory condition were examined. To assess the influence of various factors during birth, children were divided into two groups depending on mode of delivery: spontaneous vaginal delivery versus cesarean section. Levels of C-reactive protein (CRP), key pro-inflammatory cytokines (IL-1β, IFN-γ, IL-8, IL-6, TNF-α) and anti-inflammatory cytokines (IL-10, IL-4) in umbilical cord blood at day 5-7 postpartum were analyzed. Statistical hypothesis testing was performed using Mann-Whitney U test and Student's t-test.Results. The state of the immune system in healthy neonates is characterized by an increase in innate and adaptive immunity markers at birth, manifested as increased numbers of natural killer cells, expression levels of adhesion molecules (CD54) by lymphocytes, Fas receptor (CD95+, CD3+CD95+) content, immunoglobulin G (IgG), circulating immune complexes (CIC), leukocyte count, lymphocyte count, CD3+-, CD19+-cells, and complement activity while CD16+CD56+ cell counts are reduced. An elevation in both pro- and anti-inflammatory cytokines (IL-1β, IL-6, TNF-α, and IL-10) was observed against a background of decreased CRP and IFN-γ concentrations.Conclusion. Proinflammatory orientation of immune response is evident throughout the first week of life in healthy infants. In healthy children, the balance between pro- and anti-inflammatory cytokines exhibits bidirectional variability that persists over the course of the first week of life.
Keywords: cytokines; healthy newborn; spontaneous vaginal delivery